The Effectiveness of the Revised Intermittent Preventive Treatment with Sulphadoxine Pyrimethamine (IPTp-SP) in the Prevention of Malaria among Pregnant Women in Northern Ghana - Yaa Nyarko Agyeman; Sam Kofi Newton; Raymond Boadu Annor; Ellis Owusu-Dabo (Journal of Tropical Medicine)
This study investigated the effectiveness of the World Health Organization (WHO)-revised Intermittent Preventive Treatment using Sulphadoxine Pyrimethamine (IPTp-SP) dosage regimen in the prevention of malaria infections in pregnancy. The study involved a prospective cohort of pregnant women who attended the antenatal clinic in four health facilities (Tamale Teaching Hospital, Tamale West Hospital, Tamale Central Hospital, and Tamale SDA Hospital) within the Tamale metropolis. Data collection spanned a period of 12 months, from September 2016 to August 2017, to help account for seasonality in malaria. The study included 1181 pregnant women who attended antenatal clinics in four hospitals within the metropolis. The registers at the facilities served as a sampling frame, and the respondents were randomly sampled out from the number of pregnant women available during each visit. They were enrolled consecutively as they kept reporting to the facility to receive antenatal care. The participants were stratified into three groups; the no IPTp-SP, <3 doses of IPTp-SP, and ≥3 doses of IPTp-SP. The participants were followed up until 36 weeks of gestation, and blood samples were analyzed to detect the presence of peripheral malaria parasites. At the end of the study, 42.4% of the women had taken at least 3 doses of SP based on the revised WHO IPTp-SP policy. Pregnant women who had taken at least 3 doses of IPTp-SP had a malaria prevalence of 16.9% at 36 weeks of gestation, compared to 35.8% of those who had not taken IPTp-SP. In the multivariable logistic regression, those who had taken ≥3 doses of SP were associated with 56% reduced odds (aOR 0.44, CI 0.27–0.70, P=0.001) of late gestational peripheral malaria, compared with those who did not take SP. IPTp-SP served under three or more doses provided a dose-dependent protection of 56% against maternal peripheral malaria parasitaemia detectable at the later stages of gestation (36 weeks). Since the dose-dependent potency of IPTp-SP depletes with time, there is the need for research into more sustainable approaches that offer longer protection.